HIV Infection and Risk Heightened Among Female Sex Workers Who Entered the Sex Trade as Adolescents in Guatemala. - Boyce, Sabrina C.; Morales-Miranda, Sonia; Ritter, Julie; Triplett, Daniel P.; Loya-Montiel, Itzel; Silverman, Jay G. (AIDS & Behavior, 2020)
A dearth of empirical research exists on female sex workers in Central America who begin selling sex under age 18. Data were collected from adult female sex workers (N = 1216) sampled using census and modified time-location sampling in three urban centers of Guatemala. In adjusted analyses, female sex workers who entered the sex trade under age 16 years were more likely to be HIV positive (AOR = 4.6, 95% CI 1.6, 13.2), have not received HIV education in their first year of sex trade (AOR = 2.8, 95% CI 1.5, 5.5), have experienced violence to force commercial sex (AOR = 4.6, 95% CI 2.2, 9.8) and have not used condoms in their first month (AOR = 2.8, 95% CI 1.3, 6.1) , relative to those who entered as adults. An interaction between age at entry and foreign migration at entry was found for HIV risk. Efforts to prevent adolescent sex trade entry are needed and may also help to reduce HIV rates in Guatemala.